Language Policy in Multilingual and Multicultural Pakistan - seifi, pouran (Advances in Social Sciences Research Journal, 2015)
Abstract Pakistan is one of the most populous countries with diversity in language and culture. Urdu is the national language and English is the official language. The only education language in most provinces is Urdu. However, most minority language speaker are discriminated and non-Urdu languages are a sign of stigma and poverty. Language policy makers in Pakistan are recommended to mind the following points to improve communication among Pakistanis so as to lead them to respect each other’s language and culture. Education must be in mother language, all small indigenous languages should have orthography and endangered languages must be revitalized. Intercultural communication can be improved by help of media and encouraging and motivating people to learn other provinces languages. Overall, mutual intelligibility should be encouraged and enhanced in order to introduce different cultures to people. Television and Radio have crucial role in bring people in friendship from different cultures by producing movies in different languages and having music national channels. People should be aware that then can communicate by their own languages else Urdu and English because most languages in Pakistan derived from same language family. Key words: diversity, language, communication, mutual intelligibility